Antioxidant Marine Hydrolysates Isolated from Tuna Mixed Byproducts: An Example of Fishery Side Streams Upcycling - Federica Grasso; María Mercedes Alonso Martínez; Federica Turrini; Diego Méndez Paz; Rebeca Vázquez Sobrado; Valentina Orlandi; Marte Jenssen; Kjersti Lian; Junio Rombi; Micaela Tiso; Elisabetta Razzuoli; Celina Costas; et al. (MDPI AG, 2024)
The aim of this research is to propose simple and scalable processes to obtain bioactive peptides extensively hydrolyzed starting from a tuna mixed biomass. The upcycling of this powdered biomass is challenging since it comes from the unsorted industrial side streams of the tuna canning process (cooked residues from fillet trimming) after a patented mild dehydration useful for preventing its degradation until its exploitation. Two different protocols were proposed, with and without the inclusion of an exogenous enzyme (Enzymatic-Assisted Extraction, EAE), with no relevant differences in yields (24% vs. 22%) and a comparable amino acid composition. Nevertheless, the former protocol (with EAE) provided peptides with an average molecular weight of 1.3 kDa, and the second one (without EAE) provided peptides with an average molecular weight of 2.2 kDa. The two corresponding types of tuna protein hydrolysates (Enzymatic Hydrolysates (EH) and Non-Enzymatic Hydrolysates (NEH)) were characterized by proximate compositions, pH, color profile, amino acid analysis, FTIR spectra, and molecular weight distribution. In addition, several biological analyses were performed to assess their potential use as nutraceutical supplements: special attention has been paid to antioxidant activity using three different methods to quantify it. EH showed the most promising antioxidant activity which could be exploited also in other fields (e.g., biomaterials, cosmetics).